Boondon ke qissay - Nagin, Ahmed; Maliha, Rao (book group Karachi, 2002)
Boondon Ke Qissay (Stories of Raindrops) is likely a collection of short stories or poems in Urdu that revolve around the theme of rain. These stories might explore the beauty of rain, its impact on nature, and the joy it brings to people.